Weird science: affect and epistemology in contemporary literary and artistic projects - Morris, K (2014)
Contemporary cultural practices sometimes appear dispassionate, distant and clinical—committed to conceptualism or formalism. Yet works by Jacques Roubaud and Jacques Jouet (both members of the Oulipo, a group of experimental writers in France that use formal and mathematical constraints to generate new literary forms) suggest a complex relationship between epistemology and affect. This thesis argues that contemporary literary and artistic projects that appropriate the tropes of clinical procedure and experimental constraint, suggest alternative forms of knowledge that implicate the body and emotions of the experiencing subject. In these projects, affect and emotion travel through reason, logic, system and constraint and are transformed in the process. Therefore any analysis of forms of affect in these works must also consider the procedural and scientific aspect, that which makes them "projects". My research, drawing on recent work that places emphasis on affect, considers these projects as test cases often mediating between a series of dichotomies such as reason/emotion and mathematics/poetry. Curiously it is in the encounter with epistemological systems that the value of affect, embodiment and subjectivity is underscored, and this thesis interrogates the various ways that contemporary projects articulate affect almost despite themselves. By passing through a scientific impulse to inquire about and test the validity of epistemological systems, these projects underscore the role of affect in producing knowledge. This thesis insists on the continued importance of the Oulipo in contemporary culture and seeks to provide a larger, interdisciplinary context for oulipian experimentation by analysing similar works in the visual arts. This thesis has four chapters, each based on the materials that the projects themselves investigate: 1) numbers and mathematics, 2) lists, collection, and census-data, 3) itineraries and travel, 4) weather and meteorology. Projects bear witness to what the poet Lyn Hejinian has called the romance of science: its rigor, patience, thoroughness and speculative imagination (Mirage, 1983, 24) In so doing, these projects reveal forms of affect that only emerge through this 'weird science' as literary and artistic experiments.